2017
DOI: 10.4314/mmj.v28i4.3
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction and attitudes towards nursing care among nurses working at Mzuzu Central Hospital in Mzuzu, Malawi

Abstract: IntroductionNurses work at the frontlines of most healthcare systems, and their contributions are recognised as essential in delivering effective patient care.1 Providing quality nursing care is therefore an important consideration when discussing patient care standards. Nurses who are satisfied with their work and with the conditions under which care is provided are more likely to provide quality care that satisfies the patient. Literature has shown that job dissatisfaction leads nurses to have negative attit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
(35 reference statements)
2
8
0
Order By: Relevance
“…18 Inadequate compensation and lack of job satisfaction were considered among factors that may be related to their negative attitude toward the provision of care for patients living with HIV/AIDS, and our findings are in agreement with this consideration. 19 We noted that compared to the RNs, the NAs lacked adequate knowledge regarding the provision of optimal care to HIV-infected patients. This was expected since NAs study for only 1 year compared to RNs who study for 4 year (P < .001).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…18 Inadequate compensation and lack of job satisfaction were considered among factors that may be related to their negative attitude toward the provision of care for patients living with HIV/AIDS, and our findings are in agreement with this consideration. 19 We noted that compared to the RNs, the NAs lacked adequate knowledge regarding the provision of optimal care to HIV-infected patients. This was expected since NAs study for only 1 year compared to RNs who study for 4 year (P < .001).…”
Section: Discussionmentioning
confidence: 96%
“…18 Inadequate compensation and lack of job satisfaction were considered among factors that may be related to their negative attitude toward the provision of care for patients living with HIV/AIDS, and our findings are in agreement with this consideration. 19…”
Section: Discussionmentioning
confidence: 99%
“…. Professional identity, or how a doctor thinks of himself or herself as a doctor, is considered to be a key factor in the ability of health professionals to provide high-quality care to improve patient outcomes [11, 12] and is believed to mediate the negative effects of a high-stress workplace [13] and improve clinical performance [14, 15] and job retention [16, 17]. A longitudinal cohort study conducted on the junior doctors, which is a critical period of transition from medical students to professional doctors, suggested that professional identity was significantly negatively related to burnout, including personal and work-related burnout.…”
Section: Introductionmentioning
confidence: 99%
“…The level of satisfaction with their profession accounts for some instances of missed nursing care. Researchers such as Nyirenda and Mukwato (2016) validate this finding in affirming that job dissatisfaction among nurses generates negative attitudes, negligence, and malpractice. As a key person who plays a tremendous role in the delivery of excellent healthcare, nurses need to be supported by their managers in ensuring their job satisfaction.…”
Section: Discussionmentioning
confidence: 83%